PPO.55 Full dilatation caesarean section and risk of subsequent preterm birth: a case series. (9th June 2014) - Carter, J; Gibson, S; Hezelgrave, N; Shennan, AH
Abstract : Preterm birth (PTB) or mid-trimester loss is rare following term pregnancy. Caesarean section carried out at full dilatation (FDCS) is associated with increased clinical challenges 1 . The integrity of the cervix may be affected by the uterine incision performed late in labour 2, however, there are few reports of clinical outcome following this scenario. We report ten cases of women with a previous history of mid-trimester loss or early birth that was preceded by a full term FDCS. Six followed failed instrumental delivery. Seven were subsequently managed in a preterm clinic with transvaginal ultrasound assessment of cervical length from 16 weeks' gestation, or presentation, and fetal fibronectin testing from 18 weeks'. Cerclage was indicated in 4/7 (2 elective, 1 abdominal, 1 rescue). So far ¾ women have delivered at term. Of the 3 women who did not receive cerclage, one delivered preterm (29+4/40) but presented after 24 weeks and had not had cervical surveillance. Cervical surveillance was successful in avoiding a cerclage in the other two. FDCS may be a risk for subsequent PTB and pregnancy loss, particularly following failed instrumental. Aetiology may be inadvertent cervical incision or tear. Cervical surveillance plus/minus cerclage may be beneficial, and the traditional threshold for using cerclage (3 prior events) may not be necessary in this group. More research is needed into the aetiology and use of ultrasound indicated cerclage in this group. Clinicians should be made aware of this risk factor and the need for higher uterine incisions. References: McKelvey A, Ashe R, McKenna D, Roberts R. Caesarean section in the second stage of labour: a retrospective review of obstetric setting and morbidity. J Obstet Gynaecol 2010;30:264–267 Zimmer EZ, Bardin R, Tamir A, Bronshtein M. Sonographic imaging of cervical scars after Cesarean section. Ultrasound Obstet Gynecol . 2004;23:594–598. doi: 10.1002/uog.1033